Insulin-Like Growth Factor Binding Proteins in Kidney Disease - Wang, Shuqiang; Chi, Kun; Wu, Di; Hong, Quan (Frontiers in Pharmacology, 2021)
The six members of the insulin-like growth factor (IGF) binding protein family (IGFBPs) were initially considered to be the regulatory proteins of IGFs in the blood circulation, mainly as a subsequent reserve for bidirectional regulation of IGF function during environmental changes. However, in recent years, IGFBPs has been found to have many functions independent of IGFs, which can interact with many proteins other than IGFs to regulate cell growth and survival both outside and inside the cell. The role of IGFBPs in regulating transcription, inducing cell migration and apoptosis is closely related to the occurrence and development of kidney disease. What’s more, IGFBPs in tissues or circulation can also be used as a biomarker for kidney disease.